HSPICE simulation and analysis of current reused operational transconductance amplifiers for biomedical applications - Chary, Udari Gnaneshwara; Kishore, Kakarla Hari (International Journal of Electrical and Computer Engineering (IJECE), 2025)
The proposed work focuses on the design of a current-reused biomedical amplifier; it is a microwatt-level electrocardiogram (ECG) analog circuit design that addresses low power consumption and noise efficiency. As implantable devices require unobtrusiveness and longevity, the current reuse technique in this circuit effectively enhances power and noise efficiencies. Using 90 nm technology enables efficient circuit implementation, yielding promising simulation results. At 100 Hz, the noise performance reaches 62.095 nV/√Hz, while the power consumption is only 8.3797 µW. These advancements are pivotal for next-generation implantable devices, ensuring reliable operation and reducing frequent battery replacements, improving patient convenience. Moreover, the high noise efficiency ensures that ECG signals are captured with high fidelity, crucial for accurate monitoring and diagnosis. This research addresses the challenges in implantable ECG analog circuit design and sets a benchmark for future developments. The techniques employed can be adapted for other bio signal monitoring devices, broadening the impact on healthcare technology. Ultimately, this advancement contributes to more efficient, reliable, and long-lasting medical devices, enhancing patient monitoring and healthcare on a broader scale.